CRISPR-CAS SYSTEMS IN PATHOGENIC BACTERIA - Berdygulova , Z.A.; Ramankulov , Ye.M. (Eurasian Journal of Applied Biotechnology, 2018)
Developing preventive measures, diagnosing, and treating diseases caused by bacteria remains a problem worldwide. Hence, understanding the mechanisms contributing to the virulence and adaptive immune systems of pathogenic bacteria is extremely important. Moreover, Throughout evolution, pathogenic bacteria have developed many protective mechanisms against bacteria-targeting viruses. One such mechanism is the CRISPR-Cas system – a part of the bacterial adaptive immune system. Nowadays, the CRISPR-Cas system is considered the best molecular tool for gene editing in molecular biology applications. Moreover, CRISPR-Cas systems play a role in the virulence of pathogenic bacteria. The variety of these systems is amazing, as is their use in various fields of biology and medicine. In this review, we summarize different types of CRISPR-Cas systems in pathogenic bacteria and discuss the role of CRISPR-Cas in bacterial virulence and its application for biotechnology.